Deletion of C1ql1 Causes Hearing Loss and Abnormal Auditory Nerve Fibers in the Mouse Cochlea - Qi, Yue; Xiong, Wei; Yu, Shukui; Du, Zhengde; Qu, Tengfei; He, Lu; Wei, Wei; Zhang, Lingjun; Liu, Ke; Li, Yi; He, David Z.; Gong, Shusheng (Frontiers in Cellular Neuroscience, 2021)
Complement C1q Like 1 (C1QL1), a secreted component of C1Q-related protein, is known to play an important role in synaptic maturation, regulation, and maintenance in the central nervous system. C1ql1 is expressed in adult cochlear inner and outer hair cells (IHCs and OHCs) with preferential expression in OHCs. We generated C1ql1 null mice to examine the role of C1QL1 in the auditory periphery. C1ql1-null mice exhibited progressive hearing loss with elevated thresholds of auditory brainstem response and distortion product otoacoustic emission. Confocal microscopy showed that the number of nerve fibers innervating both IHCs and OHCs was significantly reduced. However, spiral ganglion neurons appeared to be normal under electron microscopy. IHC development and survival were not affected by deletion of C1ql1. Voltage-clamp recording and immunocytochmistry combined with confocal microscopy showed C1ql1-null IHCs showed no significant reduction of pre-synaptic proteins and synaptic vesicle release. This is in contrast to significant OHC loss in the KO mice. Our study suggests that C1ql1 is essential for development of hair cell innervation and OHC survival. But maturation of presynaptic machinery in IHCs does not depend on C1QL1.